2007
DOI: 10.1007/s10787-007-1605-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of some nonsteroidal anti-inflammatory drugs on experimental induced gastric ulcers in rats

Abstract: Celecoxib is a frequently used nonsteroidal anti-inflammatory drug (NSAID) in the treatment of rheumatoid arthritis and osteoarthritis. It selectively inhibits cyclooxygenase II (COX-2) enzyme which is responsible for the production of proinflammatory prostanoids. It has been proposed that since it does not significantly inhibit COX-1, an isoenzyme responsible for the production of cytoprotective prostanoids, celecoxib has fewer side effects in the stomach. Dipyrone which is a drug with potent analgesic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
11
0
8
Order By: Relevance
“…On the basis of 50% inhibitory concentration values obtained from in vitro and rat studies, it has been claimed that dipyrone might elicit a selective COX-2 inhibition that could explain why use of dipyrone, in contrast to aspirin and other NSAIDs, is not associated with an increased risk of gastrointestinal bleeding [23,24]. Acetaminophen inhibits both COX-1 and COX-2 weakly in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of 50% inhibitory concentration values obtained from in vitro and rat studies, it has been claimed that dipyrone might elicit a selective COX-2 inhibition that could explain why use of dipyrone, in contrast to aspirin and other NSAIDs, is not associated with an increased risk of gastrointestinal bleeding [23,24]. Acetaminophen inhibits both COX-1 and COX-2 weakly in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Berenguer et al (2002) did not demonstrate any effect of multiple administration of metamizole on experimentally induced gastric ulcer in rats. Moreover, Batu and Erol (2007) proved experimentally that the drug might have a protective effect against some types of gastric ulcers. They demonstrated that metamizole decreased the ulcer index of rats with histamine-and diethyldithiocarbamate-induced gastric ulcer, but it did not change the ulcer index of rats with stress-induced gastric ulcer.…”
Section: Side Effectsmentioning
confidence: 99%
“…Their results suggest that the common factor engaged in the protective effect of the drug could be its ability to increase synthesis and/or release of gastric mucus. In addition, some of the protective effect of metamizole may be paradoxically due to its ability to increase the gastric PGE 2 content (Batu and Erol 2007). Thus, regarding the influence on the digestive tract, metamizole seems to be much safer than NSAIDs.…”
Section: Side Effectsmentioning
confidence: 99%
“…Представляет собой производное пиразолона (Brogden, 1986 . В свете того, что мы знаем сегодня, последняя классифика-ция представляется ошибочной, так как в отличие от НПВС механизм, через который действует мета-мизол, опирается на ингибирование центральной циклооксигеназы-3 (ЦОГ-3), активацию и модуля-цию системы опиоидных нейропептидов и системы каннабиноидов [3,4]. Метамизол является проле-карством, которое спонтанно распадается после перорального введения на структурно родственные соединения пиразолона.…”
Section: ам овечкин 2001unclassified